Evaluation of ASGR p779/p780 primers in the determination of aposporic apomixis in Cenchrus purpureus - Hernández Montesinos, A. R.; Recio, María E.; Carvajal-Yepes, Mónica; Arango, J.; Rodríguez Alfonso, Daymara; Fortes González, Dayleni; Herrera García, R. S. (Cuban Journal of Agricultural Science, 2025)
The objective of this study was to evaluate the molecular markers ASGR p779/p780, specific for aposporic apomixis, in the determination of the type of reproduction in accessions of Cenchrus purpureus. The study was conducted at the Alliance of Bioversity International and the International Center for Tropical Agriculture. The samples under study come from 62 accessions of C. purpureus from the Germplasm Bank of Grasses and Forages of Instituto de Ciencia Animal. The type of reproduction of the accessions was determined by Polymerase Chain Reaction (PCR) with the combination of direct and reverse primers p779/p780 completely linked to the aposporic apomixis. It was not obtained DNA amplification from the C. purpureus accessions and the Urochloa spp. controls that were negative for aposporic apomixis. However, DNA amplification was obtained from positive controls to aposporic apomixis in Urochloa spp. accessions reported as apomictic. The amplification products revealed a well-defined polymorphic band on the gels with an approximate size of 950 base pairs. The p779/p780 primers amplified the apomixis-positive Urochloa accessions, but did not amplify the negative controls or the C. purpureus accessions. These results suggest that (I) or the 62 accessions of C. purpureus from ICA reproduce sexually and do not exhibit aposporic apomixis, or that (II) the primers are not specific to this species.